Outdoor education to strengthen the implementation of sustainable development - Jagodzińska, Małgorzata; Strumińska-Doktór, Anna (Studia Ecologiae et Bioethicae, 2019)
The disadvantage of education in the current school system is verbal communication as well as research and experiments conducted at school. Students have very few opportunities to conduct research and experience reality in a natural environment. Active participation awakens their interest and gives them a sense of authorship. Joint planning of expeditions, trips and field games is a factor that shapes bonds and trust in the group. Outdoor activities allow the discovery the interests and talents. Outdoor education (OE) has become increasingly popular and has various names in Poland, such as outdoor education, non-classroom education, field education, field classes and adventure pedagogy. During the field classes, children acquire both knowledge and skills. The basics are group activities, including outdoor team games. Natural obstacles are used, and the natural environment contains a wealth of teaching aids. Outdoor learning through experiencing reality allows for understanding the laws of nature, which clearly generate an approach of sustainable development in human life. Unfortunately, students are not prepared to undertake outdoor tasks, and young teachers rarely organise trips, considering them recreation and breaks from learning rather than as opportunities to learn. Teacher awareness of new trends in education, including outdoor education, is growing, but the competencies related to conducting outdoor classes have not changed along with it. The paper will present the results of research conducted among pre-school and early childhood education students in Białystok and Łódź. The objective of the research was to gather information on the OE knowledge of students and their expectations with it in the context of shaping and improving the quality of education.